2021
DOI: 10.3390/antiox10020180
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Natural Functional Ingredients from Olive and Citrus Extracts in Spanish-Type Dry-Cured Sausage “Fuet”

Abstract: The main objective of the present study was to evaluate the antioxidant capacity of hydroxytyrosol derived from synthetic (HTs) and organic (HTo) sources, and citrus (C) extract, by incorporating them in a dry-cured meat product: fuet. Firstly, antioxidant extracts were tested in an oxidized pork meat model system, avoiding by 100% the protein oxidation against AAPH and AMVN. After that, four batches of fuet were made, namely Control, HTs, HTo, and C, which incorporated antioxidant extracts as substitutes of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Firstly, 200 ppm of HXT, from both origins, reduced the microbial growth, the protein and the lipid oxidation being the synthetic HXT the only that did not alter the sensory quality of fresh lamb burgers for 6 days at 4 • C [58]. In this manner, we tested these extracts also a dry-cured pork sausage ('fuet') obtaining similar results [59]. In this sense, although on these days society prefers natural products than synthetic, the stability of the natural isolated HXT may have lower and limited stability, which may reduce its bioactivity.…”
Section: New Trends: Natural Vs Synthetic Hydroxytyrosolmentioning
confidence: 99%
“…Firstly, 200 ppm of HXT, from both origins, reduced the microbial growth, the protein and the lipid oxidation being the synthetic HXT the only that did not alter the sensory quality of fresh lamb burgers for 6 days at 4 • C [58]. In this manner, we tested these extracts also a dry-cured pork sausage ('fuet') obtaining similar results [59]. In this sense, although on these days society prefers natural products than synthetic, the stability of the natural isolated HXT may have lower and limited stability, which may reduce its bioactivity.…”
Section: New Trends: Natural Vs Synthetic Hydroxytyrosolmentioning
confidence: 99%
“…On the other hand, another study concluded that omega‐3 enrichment together with different amounts of HTX (100, 200, and 400 ppm) increased the antioxidant capacity in pies and caused a decrease in lipid oxidation on days 3, 6, and 9 (Muíño et al., 2017 ). More recently, HTX has demonstrated to be highly antioxidant compound in lamb patties (Martínez‐Zamora et al., 2020 ), chicken Nuggets (Martínez, Ros, & Nieto, 2020 ), and dry cured sausages (Zamora et al., 2021 ). In this sense, the high antioxidant capacity of this compound, despite its concentration being the lowest of all the extracts, can be explained by the presence of an OH group on its benzene ring, for which a higher function as a free radical scavenger, increasing its antioxidant power as well as its efficacy under stress conditions (Martínez et al., 2018 ; Martínez‐Zamora et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ten healthy subjects (five females, five males, aged 20–50) were trained according to the ISO8586:2012. A 4‐point hedonic scale (Martínez Zamora et al., 2021) was used to evaluate the color, texture, flavor, appearance, aroma, aftertaste and overall acceptability of the samples from 1 (minimum: I do not like it) to 4 (maximum: I like it very much/I would buy it).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, synthetic antioxidants are commonly used in the food industry to control oxidation reactions. Due to concerns about toxicity, research is underway to use natural antioxidants that do not produce these harmful health effects (Martínez Zamora et al., 2021).…”
Section: Introductionmentioning
confidence: 99%